Life sustainable, programmable, bottom-up manufacturing - Hessel, Andrew (O'Reilly Media, 2015)
The future of manufacturing will be self-assembling products. It is said that life is nanotechnology that works-matter assemblers that are not theoretical. Long before industrial revolution, the assembly line, and mass-manufacturing, there were living systems. They successfully populated every energetic niche on the planet with products so technologically advanced and complex that to this day many attribute their design and manufacture to deities. In practical terms, these biological machines are made from non-toxic, commonly available precursors, do not require extreme temperatures or pressures, and are infinitely renewable-characteristics that we will need to apply to the manufacturing of more and more products if humanity is ever to achieve true sustainability. Science has been systematically deciphering the mechanisms of life for centuries, a process of reverse engineering that has been accelerating alongside our ability to manipulate at the micro- and nano-scale. Now, with many of the fundamental systems understood, and the conserved programming language of DNA deciphered, the ability to directly and reliably engineer biological systems and products is coming online. While it is still early days, biocoding and biomanufacturing looks to be one of the most powerful and compelling tools we've ever had to address global needs and challenges, one that will touch virtually every facet of human activity and enterprise. The Autodesk Bio/Nano Programmable Matter group is developing design tools for this space and integrating them with other domains and scales of computer-aided design and manufacturing.
Includes bibliographical references. - Online resource; title from title page (Safari, viewed December 4, 2018)
Keywords: Sustainable development; Manufacturing industries -- Environmental aspects; Développement durable; Industrie manufacturière; Aspect de l'environnement; sustainable development; Manufacturing industries; Environmental aspects